Strategi Dinas Sosial Dalam Pemberdayaan Penyandang Disabilitas Melalui Program Graha Nawasena (Rumah Harapan Disabilitas) di Kota Denpasar - Shanti, Ni Made Dwita Purnama; Lukman, Juwita Pratiwi; Yudartha, I Putu Dharmanu (Lenggogeni Data Publishing, 2025)
Fulfillment of the rights of persons with disabilities is regulated in Regional Regulation No. 11 of 2022. As a form of implementation, the Social Service together with the Denpasar City Government established Graha Nawasena. This study aims to analyze the strategy of the Denpasar City Social Service in optimizing the empowerment of persons with disabilities through the Graha Nawasena program. This study uses a descriptive qualitative method with data collection techniques through interviews, observations and documentation. The results of this study indicate that the strategy used by the Social Service in terms of empowering persons with disabilities has been running quite well, although in its implementation it is still not optimal. This can be seen from the five indicators of the strategy used which have been running quite well. The SWOT analysis produces four main strategic recommendations: (1) Strengthening the implementation of Denpasar City Regional Regulation No. 11 of 2022 by optimizing collaboration with stakeholders, mass media, and educational institutions (SO), (2) Improving disability-friendly infrastructure to attract stakeholders, mass media and educational institutions by applying for grant funds and CSR programs (WO), (3) Maintaining the formation of Graha Nawasena to ensure the sustainability of the program by developing a more independent business model (ST), (4) Strengthening the involvement of all internal members of the organization by providing education and training on product marketing (WT). Abstrak Pemenuhan hak penyandang disabilitas diatur dalam Perda No. 11 Tahun 2022. Sebagai benuk implementasinya, Dinas Sosial bersama Pemerintah Kota Denpasar membentuk Graha Nawasena. Penelitian ini bertujuan untuk menganalisis strategi Dinas Sosial Kota Denpasar dalam mengoptimalkan pemberdayaan penyandang disabilitas melalui program Graha Nawasena. Penelitian ini menggunakan metode kualitatif deskriptif dengan teknik pengumpulan data melalui wawancara, observasi dan dokumentasi. Hasil penelitian ini menunjukkan bahwa strategi yang digunakan oleh Dinas Sosial dalam hal pemberdayaan penyandang disabilitas sudah berjalan cukup baik, meskipun dalam pelaksanaanya masih belum maksimal. Hal ini dapat dilihat dari kelima indikator strategi yang digunakan telah berjalan cukup baik. Analisis SWOT menghasilkan empat rekomendasi strategi utama: (1) Memperkuat implementasi Peraturan Daerah Kota Denpasar No. 11 Tahun 2022 dengan mengoptimalkan kolaborasi bersama pemangku kepentingan, media massa, dan lembaga pendidikan (SO), (2) Memperbaiki infrastruktur yang ramah disabilitas untuk menarik pemangku kepentingan, media massa dan lembaga pendidikan dengan mengajukan dana hibah dan program CSR (WO), (3) Mempertahankan pembentukan Graha Nawasena guna memastikan keberlanjutan program dengan mengembangkan model bisnis yang lebih mandirI (ST), (4) Memperkuat keterlibatan seluruh anggota internal organisasi dengan memberikan edukasi dan pelatihan mengenai pemasaran produk (WT). Kata Kunci: Graha Nawasena, SWOT, Strategi, Pemberdayaan Penyandang Disabilitas